E-Commerce and Digital Markets: A Literature Review on Opportunities and Challenges of Change Management in Information Technology - Yurika Narulita Maulidya Yurika (Institute of Information Technology and Social Science (IITSS), 2023)
This article aims to empirically describe change management in the digital era from the perspective of organizational opportunities and challenges. The method employed is a literature study using a qualitative approach. The researcher collected relevant scientific articles from ScienceDirect and Google Scholar using the keywords change management, digital era, challenges, and opportunities to support the conceptual analysis. The findings indicate that factors influencing change include knowledge, skills, trust among organizational members, and the organizational environment. The challenges in implementing change generally stem from resistance, which can be categorized into individual and organizational resistance. Individual resistance includes habits, the need for security, economic factors, fear of the unknown, and perception. Overall, this study emphasizes that managing change in the digital era requires adaptability, strategic use of information technology, and leadership capable of aligning organizational transformation with digital opportunities.